Cooperatives in Ukraine: Applicative Peculiarities of Legal Integration up to the EU Standards - VASYLIEVA, Valentyna A.; ZELISKO, Alla V.; ZOZULIAK, Olga I. (Journal of Advanced Research in Law and Economics, 2018)
The article deals with the peculiarities of the processes of adaptation of the legal regulation of cooperatives in post-socialist states (as exemplified by Ukraine) to the requirements of the European Union. Such features are formed taking into account historical, social and economic prerequisites of the development of the modern legal framework of Ukraine. Authors are focused on problems of pecuniary autonomy of cooperatives; the possibility of its full-fledged activities as the parties to market relations; implementation of legal mechanisms that can increase competitive advantage of cooperatives in present-day conditions; increase the level of security and protection of rights and interests of cooperative members. It is proved that the effective entrepreneurial activity of the cooperative is rather compatible with the social nature of the latter, moreover – it contributes to the implementation of such a nature. Behind the arguments in favor of such an approach there is the principle declared in the practices of the European Union law – the focus of cooperatives on the affirmation of the interests of its members.